Experimentation of Interactive Setting Cooperative Learning Model (PSIK) and Course Review Horey (CRH) on The Material Geometry Flat Side Reviewed from Student Intelligence in The SMP N in Districk of Demak - Nugroho, Muhamad Asif Cahya Aji; Budiyono, Budiyono; Slamet, Isnandar (Kreano, Jurnal Matematika Kreatif-Inovatif, 2019)
The purpose of this study is to find out from each model of learning mathematics, which provides better mathematics learning achievement, students who have the type of logical intelligence mathematics, visual, kinesthetic or interpersonal. This research method of this study is quasi experimental research or pre-experimental research with research design using 3 x 4 factorial designs. The population in this study is the entire students VIII grade SMP N in districk of Demak. Sampling was done by stratified cluster random sampling technique. Instruments used to collect data are a questionnaire of multiple intelligences and mathematics learning achievement test. The prerequisite test includes the population normality test using the Lilliefors method and the homogeneity test of population variance using the Bartlett method.With α = 0, 05. Hypothesis testing of the study are analysis of variance with unequal cell. Based on the results of hypothesis testing, obtained the conclusion that. There is interaction of learning model on mathematics learning achievement in each category of students’ multiple intelligence.